Economic Value of non-Timber Forest Product Utilization at Padali Resort, Ujung Kulon National Park - Gusti Mahendra; Harnios Arief; Tutut Sunarminto (Media Konservasi, 2018)
The National park has a supporting  function in order to improve the society's welfare and their quality of life. One of the activities that can be carried out to support this function is the utilization of the potential of non-timber forest products. This research aims to identify the type and economic value of NTFP utilization at the Padali Resort in Ujung Kulon National Park. This research was carried out at TNUK Padali Resort and the village which guided under of the Paduk TNUK Resort in March to April 2018. The methods used were literature studies, interviews and field observations. Analysis of the data used is descriptive and quantitative analysis to calculate the economic value of NTFP utilization through a market price approach. The types of NTFPs used by the community consist of 8 types, namely sugar palm, bamboo, durian, dogfruit, coconut, mangosteen, melinjo and stink bean with a total economic value of Rp. 262,460,702.25 / year. The majority of NTFPs (62.62%) utilized by the community are for commercial purposes. Padasuka Village has the greatest dependence on NTFPs in the Padali Resort area with a percentage of 50% of the total economic value of NTFP utilization at Padali Resort TNUK. Keywords: buffer zone communities, economic value, non timber forest product, utilization